CORRELATION OF HYPERNATREMIA TO SUCCESS RATE OF SKIN GRAFT IN BURN PATIENTS DR. SOETOMO GENERAL ACADEMIC HOSPITAL BURN CENTER FROM 2014-2018 - Wulandari, Ephora Christina; Lynda Hariani; Budi, Agus Santoso (Universitas Airlangga, 2019)
Highlights: Patients with hypernatremia had a relative risk of experiencing graft failure, especially if the graft involved more than 10% of the affected area. The importance of managing electrolyte imbalances to enhance the success of skin graft procedures. Abstract: Introduction: From collective data from 2014 – 2018 from Burn Center in Dr. Soetomo General Academic Hospital, the rate of failed skin graft was 26%. This high number became a concerned because skin graft was the main procedure to close large burn wound. This event is affected by many problems, one of them is electrolyte imbalance. Hypernatremia was seen in major burn patients that causes the disruption of wound healing process of skin graft. Methods: A cross sectional study of patients with burns admitted to the Burn Centre of Dr. Soetomo Hospital between January 2014 and December 2018 were evaluated. Results : 143 subjects were involved in this study. 44 subjects are female (31%) and 99 subjects are male (69%). 66% of the burn injuries are caused by fire (93 subjects), 14% caused by electricity (20 subjects), 8% caused by scald (12 subjects), 6% caused by boiled oil (8 subjects), 4% caused by chemical agent (6 subjects) and 2% caused by blast injury (1 subject). 77% of all subjects (110 subjects) underwent split thickness skin graft less than 10% while 23% (33 subjects) underwent the procedure 10% or more than it. Hypernatremia is found in 16% of all subjects (23 subjects), 19% with hyponatremia (28 subjects) and majority of it, 65%, with normonatremia (92 subjects). From the study, it was found that the risk of failed skin graft was higher on hypernatremia subjects than normonatremia subjects, the relative risk was 6,06 to fail. This number was higher if the skin graft procedure took more than 10%. But, it was found the risk was higher on hyponatremia subjects than the rest of subjects, with the relative risk was 7.75 to fail. Conclusions: Hypernatremia caused high risk of failed skin graft on major burn patients.